Solo Practice Physicians in Georgia - Fedelis Mutiso; Emmanuel Akowuah; Samuel Opoku; Bettye Apenteng (Journal of the Georgia Public Health Association, 2017)
Background: Office-based physicians can practice in a solo or group setting. Solo physician practices are staffed by a single physician who is responsible for all the care of the patients. Physicians in solo practices are also responsible for the infrastructure, personnel and investment cost of their practices. Further, evidence suggests that physicians in solo practices are more likely to be dissatisfied with their medical career compared to those in group practices. Given these challenges, current trend suggests a shift away from solo physician practices. However, there are still physicians in solo practices in Georgia but little is known about them. This study attempts to characterize the physicians working in solo practices and in so doing, add to the growing knowledge of the healthcare workforce in Georgia. Methods: The 2014 Physician Compare data were used for this study. This database contains information on individual physician level characteristics including gender, credential, primary specialty and practice type. The data were linked to the 2014 Area Resource File to provide information on the rural/urban location of physician practices. Physician practices were classified as rural or urban based on the Economic Research Service classification. Chi square and t-tests were carried out to examine the characteristics of physicians practicing in solo practices. Statistical analyses were conducted in StataMP 14. Results:Of the 13,499 Georgia physicians studied, 1448 physicians were in solo practices. The majority of these physicians were in urban areas (78.30%; pConclusions: There are a large number of physicians in solo practices in Georgia. Given the challenges facing these physicians, it is important for Georgia to consider approaches to decrease the burden on physicians working in solo practices. Key words: solo practices, physicians, Georgia healthcare workforce